RARE PRESENTATION OF ACUTE MYELOID LEUKAEMIA IN A SUDANESE CHILD - Musa, ShamsElFalah; Magzoub, Mamoun; Gusm Elbari Ahmed, Elbashir; Haroun, Huda (مجلة الجزيرة للعلوم الصحية; مجلد 7 عدد 1 (2011), 2011)
Classically, children with acute leukaemia present with symptoms and signs related to infiltration of the bone marrow by leukaemic cells, such as fever, pallor and fatigue, cutaneous and mucosal bleeding and bone pain. Also anorexia and weight loss. This is a case of acute myeloid leukaemia (AML.) which presented with tongue bleeding and then part of the tongue separated completely from the rest of the tongue and it fell from his mouth, few days later it regenerated to a normal tongue. Few days after regeneration of the right side of the tongue, the same previous scenario occurred in the left side, and then regenerated to normal size. This indicates an unusual presentation of AML.